Gel Preparation Using Matoa Leaf (Pometia pinnata) Ethanol Extract: Formulation and Physical Evaluation - Vonny Kurnia Utama; Yan Hendrika; Fuji Astuti (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2022)
Matoa leaves (Pometia pinnata) contain antioxidants that can prevent premature aging due to free radical damage to skin cells, reduce dark spots, acne, and improve collagen performance in the skin. The gel preparation was chosen because it provides a feeling of coolness, moisture, and good absorption on the skin and is easily washed off with water. The purpose of this research is to create a gel formula and conduct a physical evaluation of the ethanol extract of matoa leaf gel. This study employed an experimental method in which gel preparations were made from ethanol extract of matoa leaves at concentrations of 2%, 3%, and 4%. The organoleptic test results are thick, clear, light green, dark green, and dense dark green, with a distinct smell of ethanol extract of matoa leaves. F0, F1, F2, and F3 all pass the homogeneity test. The pH test results for F0, F1, F2, and F3 are 4-5. F0, F1, F2, and F3 dispersion tests were 6.1 cm, 5.3 cm, 5.7 cm, and 5.5 cm, respectively. As a result, the ethanolic extract of matoa leaves can be formulated as a gel preparation with favorable physical results.